Barrier-free campus: University Malaya, Kuala Lumpur - Mohamed Osman, Mariana; Muhd Radzi, Fatimah Husna; M Bakri, Nurul Izzati; Ibrahim, Mansor; Ahmad Thani, Siti Nur 'Alia (Elsevier, 2014)
Currently, the provisions of the barrier free facilities are not well distributed and insufficient in the campus area. The university authorities neglected and not well maintained the existing facilities. This research highlighted the importance of the barrier free design and facilities from the PwDs perspective. Mean score analysis is used to measured the condition of facilities from PwDs point of view. Some of the selected area had low mean score and in need of improvement. Hence, the recommendations were suggested to improve the condition of barrier-free facilities.